Adat in the Discourse of “Lived Religion”: Local Wisdom as a Model of Indigenous Religion Recognition in Indonesia - Balla Nggiku, Emanuel; Lattu, Izak Yohan Matriks; Bartalis, Kata-Szilvia (Department of Religious Studies, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2024)
This research examines local wisdom as a model for recognizing indigenous religions within the context of interfaith encounters through adat practices. While Indonesia’s diversity of beliefs is a significant cultural asset, it can also become a source of conflict if not properly managed, particularly concerning the recognition of indigenous religions. Indigenous religions serve as guardians of local wisdom and play a crucial role in fostering social cohesion. Therefore, the application of local wisdom through adat practices is vital for facilitating interfaith encounters in everyday life, aligning with the concept of lived religion. The interpretation of local wisdom and the practice of traditional ceremonies—comprising rituals, symbols, and oral narratives—play a pivotal role in acknowledging the existence and value of indigenous religions. By focusing on the case of Marapu, indigenous religion in Sumba, this research highlights the importance of recognizing indigenous religions within the broader Indonesian context. The study employs a qualitative methodology with a critical ethnographic approach, utilizing data collected through observation, in-depth interviews, and literature review. The findings reveal that adat, as a lived religious practice among the people of Sumba, serves as a “womb” capable of providing social recognition for Marapu. Within the Christian-Marapu encounter, significant interpenetration occurs during the implementation of adat, emphasizing the deep entwinement of cultural practices and belief systems in sustaining mutual respect and coexistence.